2017
DOI: 10.9778/cmajo.20170038
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional population-based study of breast cancer screening among women with HIV in Ontario, Canada

Abstract: Background:As women with HIV live longer, the need for age-appropriate breast cancer screening will increase. We compared rates of screening mammography among women with and without HIV. Methods:We used administrative health databases to identify all women in Ontario, Canada, who were eligible for screening mammography (aged 50 to 74 yr and no history of breast cancer) as of Apr. 1, 2011. We used multivariable log-binomial regression to compare the 2-year period prevalence of screening mammography in 2011 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In addition, Tron and colleagues and Kendall et al identified specific barriers for screening among women living with HIV, including low educational background and low income level. 10,11 These challenges are identical to those identified in the review by Lambert et al, who studied barriers to cervical cancer screening among women with HIV. 22 Thus, social determinants of health play a major role in the receipt of cancer screening among HIV-infected women and may contribute to disparities in cancer care.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In addition, Tron and colleagues and Kendall et al identified specific barriers for screening among women living with HIV, including low educational background and low income level. 10,11 These challenges are identical to those identified in the review by Lambert et al, who studied barriers to cervical cancer screening among women with HIV. 22 Thus, social determinants of health play a major role in the receipt of cancer screening among HIV-infected women and may contribute to disparities in cancer care.…”
Section: Discussionmentioning
confidence: 60%
“…911 Two studies were cross-sectional, and 1 used a prospective cohort design. All 3 studies were scored as good quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the context of the younger patient and the sub‐Saharan African setting, benign breast disease, tuberculosis and, occasionally, Kaposi sarcoma of the breast add to diagnostic challenges. Turning to higher‐income countries, attendance of breast cancer screening among WLWHA was higher than that of the general population in France, but lower in Ontario, Canada, thus a setting‐specific evaluation of early‐diagnosis interventions needed in WLWHA is warranted.…”
Section: Discussionmentioning
confidence: 99%